TRACEM - Towards a Standard Metamodel for Execution Traces in Model-Driven Reverse Engineering - Pereira, Claudia Teresa (2022)
Reverse engineering is a crucial stage in the software modernization process. The current techniques available in existing CASE tools provide forward engineering and limited facilities for reverse engineering, dynamic analysis in particular. The Architecture-Driven Modernization initiative has defined standards to support the modernization process in the model-driven engineering (MDE) context. Standardization increases interoperability between different tools enabling a new generation of solutions to benefit the whole industry and encourage collaboration among complementary vendors. In this paper, we present TRACEM, a metamodel to represent trace information under a standard representation. This metamodel complements a MDE framework for software modernization that aims to integrate static and dynamic analysis techniques during the reverse engineering process. This paper includes a case study that exemplifies how dynamic information combined with static information allows improving the whole reverse engineering process.